Isolated Asymptomatic Hyperbilirubinemia Among Healthy Blood Donors – A Menace - Senthil E; Mangaiyarkarasi Amirthalingam (Online Journal of Health & Allied Sciences)
Background: Visual inspection of plasma and platelet components is a crucial step in quality assessment at blood centres, enabling the identification of high-coloured plasma units. High-coloured units require further investigation through bilirubin testing. Normally, serum bilirubin levels range from 0.1-1.2mg/dl, with the majority being unconjugated (0.1-1.0mg/dl). Elevated bilirubin levels occur when systemic circulation bilirubin exceeds normal ranges, typically manifesting as jaundice at serum bilirubin levels ≥2.5mg/dl. Materials and Methods: This prospective observational study was conducted at the Department of Blood Transfusion Medicine, Government Coimbatore Medical College and Hospital. A total of 8,454 units were collected during the study period. Plasma and platelet component bags showing high-yellow coloration were included and subjected to serum bilirubin level estimation to detect hyperbilirubinemia. Serum total bilirubin levels >1.2mg/dl were considered significant. Results: During the seven-month period, 40 units (0.47%) exhibited icteric characteristics. All 40 icteric units tested negative for Transfusion-Transmitted Infections (TTI) screening. Further investigation revealed that elevated serum bilirubin levels were attributed to increased indirect bilirubin, predominantly unconjugated. Conclusion: Our study suggests that, despite lacking evidence of adverse effects from transfusing blood with highly coloured plasma, our institution will continue to discard such components until sufficient safety evidence emerges. Donors with isolated asymptomatic unconjugated hyperbilirubinemia should be referred for medical follow-up. Regulatory authorities should re-evaluate existing policies and consider incorporating serum bilirubin testing with defined cutoff limits into routine blood component screening.